THE EFFECT OF BRAND IMAGE AND BRAND TRUST ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY OF ARA SHOP SIDOARJO - Arum Dwi Dayanti; I Nyoman Sudapet; Hamzah Deny Subagyo (NAROTAMA UNIVERSITY, Indonesia, 2019)
The purpose of this study was to analyze the influence of brands image and brand trust on customer satisfaction and customer loyalty in Ara Shop, Sidoarjo. This research is quantitative research. The population and samples were distributed by 60 respondents. Technique of answering data using a questionnaire. Analysis of the data used is Convergence Validity, Discriminant Validity, used and Average Variance Extracted (AVE). Based on the results of the study, the brand image variable and brand trust simultaneously or partially significant towards customer satisfaction and customer loyalty in Ara Shop, Sidoarjo.